Photovoltaic-thermal system for building application: a case study - ATMACA, MUSTAFA (TAYLOR & FRANCIS INC, 2022)
In buildings today, there is also a need of thermal energy, besides electrical energy. Hot air and hot water are forms of thermal energy that can be used in buildings. PV/T systems help produce these shapes of energies with the use of solar power. In this study, the supply of the required energy in buildings produced by a PV/T system, using two working fluids - air and water - has been investigated. The studies were conducted on typical winter, spring, and summer days which had different atmospheric conditions. At the same time, the amount of electrical and thermal energy gained between the selected intervals on those days was also investigated. The results show that the energy obtained in three different ways from a PV/T module are well high. The produce of hot air can be used as a residential need in winter. The results also show that a great portion of the need to heat a typical office up to 59% and to provide 55% of hot water consumption for one person on a daily basis in only 1 h can be provided by such a PV/T module. Additionally, the energy which is gained from air is well high in summer and can be used for other purposes by way of optimization. On the other hand, the production of electrical energy and hot water can also be used for residential needs in all seasons.
Keywords: Air and water based PV; T system; building energy need; different climatic conditions; SOLAR COLLECTOR; PERFORMANCE; PV/T; ENERGY